Electrospun BiFeO3 Nanofibers for Vibrational Energy Harvesting Application. Issue 7 (18th January 2022) - Ichangi, Arun; Lê, Khan; Queraltó, Albert; Grosch, Matthias; Weißing, René; Ünlü, Feray; Chijioke, Amadi Kingsley; Verma, Anjneya; Fischer, Thomas; Surmenev, Roman; Mathur, Sanjay
Abstract : Bismuth ferrite (BiFeO3, BFO) has found application in a wide range of fields owing to its fascinating multiferroic properties. Herein, the interplay between the piezoelectric properties and morphology of BFO nanostructures is exploited for vibrational energy harvesting application by tailoring BFO to a high aspect ratio and high surface area nanofiber morphology. This work demonstrates a facile pathway for the fabrication of high‐performance flexible nanogenerators, based on BFO nanofibers, from a cost‐effective and energy‐efficient electrospinning technique. The X‐ray diffraction data of calcined fibers confirm the formation of noncentrosymmetric crystalline perovskite phase. The morphological characterization by scanning electron microscopy shows a compact anisotropic nanofibrous morphology. For the fabrication of nanogenerators, BFO nanofibers are embedded in a piezoactive polymer matrix (polyvinylidenfluoride [PVDF]). As‐fabricated BFO/PVDF composite nanogenerators produce a high peak‐to‐peak voltage output of 7.6 V, with an average output power density of 185 ±  106 nW cm −2 upon periodic application of force through finger knocking. Abstract : Piezoelectric nanogenerators based on electrospun BiFeO3 nanofibers in a poly(vinylidene fluoride) (PVDF) polymer matrix are examined for their suitability in vibrational energy harvesting applications. The unique advantages of nanofiber morphology in terms of high aspect ratio and surface area promote the power output characteristics of the devices.